Entrepreneurs’ secrets and trade secrets in cases concerning access to public information (Ius Novum, 2021)
An entrepreneur’s secret is one of the grounds on which access to public information canbe refused. Administrative courts’ case law stipulates that two elements jointly constitutean entrepreneur’s secret: a tangible one, e.g. a detailed description of the method of serviceprovision, its price and technical conditions of an undertaking, and a formal one, i.e. the willto make some information data secret.
Keywords: trade secret; entrepreneur’s secret; access to public information; decision to refuse access to public information